Promastigote secretory gel from natural and unnatural sand fly vectors exacerbate Leishmania major and Leishmania tropica cutaneous leishmaniasis in mice - Giraud, E; Svobodová, M; Müller, I; Volf, P; Rogers, M E (Parasitology, 2019)
Leishmania rely heavily on glycans to complete their digenetic life cycle in both mammalian and phlebotomine sand fly hosts. Leishmania promastigotes secrete a proteophosphoglycan-rich gel (Promastigote Secretory Gel, PSG) that is regurgitated during transmission and can exacerbate infection in the skin. Here we explored the role of PSG from natural Leishmania-sand fly vector combinations by obtaining PSG from Leishmania (L.) major-infected Phlebotomus (P.) papatasi and P. duboscqi and L. tropica-infected P. arabicus. We found that, in addition to the vector's saliva, the PSG from L. major and L. tropica potently exacerbated cutaneous infection in BALB/c mice, improved the probability of developing a patent cutaneous lesion, parasite growth and the evolution of the lesion. Of note, the presence of PSG in the inoculum more than halved the prepatent period of cutaneous L. tropica infection from an average of 32 weeks to 13 weeks. In addition, L. major and L. tropica PSG extracted from the permissive experimental vector, Lutzomyia (Lu.) longipalpis, also exacerbated infections in mice. These results reinforce and extend the hypothesis that PSG is an important and evolutionarily conserved component of Leishmania infection that can be used to facilitate experimental infection for drug and vaccine screening.
Keywords: Leishmania major; Animals; Proteoglycans; protozoální proteiny; Female; leishmanióza kožní; ženské pohlaví; sliny; proteoglykany; Protozoan Proteins; Phlebotomus; syndrom vzplanutí nemoci; Mice; kůže; membránové proteiny; Mice, Inbred BALB C; myši; Leishmania tropica; Leishmaniasis, Cutaneous; Parasite Load; Saliva; Skin; myši inbrední BALB C; Membrane Proteins; Symptom Flare Up; zvířata; parazitární zátěž